2001
DOI: 10.1063/1.1351157
|View full text |Cite
|
Sign up to set email alerts
|

Light induced structures in liquid crystalline side-chain polymers with azobenzene functional groups

Abstract: We applied ellipsometry to study the distribution of azobenzene fragments in the films of two types of comblike polymers with azobenzene moieties in the side chains before and after ultraviolet (UV) light irradiation. The polymer with an alkyl chain at the end of the azobenzene fragment forms structures with preferred homeotropic alignment of the fragments. Irradiation of this polymer with nonpolarized UV light at normal incidence induces a homeotropic alignment of azobenzene fragments. Oblique irradiation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 22 publications
2
51
0
Order By: Relevance
“…The stable POA was observed later on in polymers containing chemically linked azochromophores (azopolymers) [4]. It turned out that stable anisotropy can be induced in both amorphous and liquid crystalline (LC) azopolymers [4,5,6,7,8,9,10]. The efficiency of POA in LC azopolymers is generally much higher than it is for amorphous homologues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stable POA was observed later on in polymers containing chemically linked azochromophores (azopolymers) [4]. It turned out that stable anisotropy can be induced in both amorphous and liquid crystalline (LC) azopolymers [4,5,6,7,8,9,10]. The efficiency of POA in LC azopolymers is generally much higher than it is for amorphous homologues.…”
Section: Introductionmentioning
confidence: 99%
“…[18] was found to be an experimental technique particularly suitable to characterize light induced anisotropy of orientational structures in azopolymer films. We have investigated these structures depending on the polarization state of the actinic light [10] and on the molecular constitution [15]. It was additionally found that the kinetics of POA involving both uniaxial and biaxial structures can be theoretically described by using the phenomenological approach suggested in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We use the results of general analysis to formulate a simple model of the photoinduced ordering in LC azopolymers. In addition to the long term stability of POA, this model accounts for biaxiality of the photoinduced orientational structures [4,17,18,19,20,21] that was neglected in the models of Refs. [7,8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The director of a liquid crystal phase can be modified by orienting chromophores doped into the phase (Sun et al, 1992;Anderle et al, 1991) by using an azobenzene-modified ''command surface'' (Chen and Brady, 1993;Ichimura et al, 1993;Gibbons et al, 1991), using azo copolymers (Wiesner et al, 1991), and, of course, in pure azobenzene LC phases (Hvilsted et al, 1995;Stumpe et al, 1991). One can force the LC phase to adopt an in-plane order (director parallel to surface), homeotropic alignment (director perpendicular to surface), tilted or even biaxial orientation (Yaroschuk et al, 2001). These changes are fast and reversible.…”
Section: Classes Of Azobenzene Systemsmentioning
confidence: 99%